Communication Barriers to Sustainable Utilization of Coconut Waste in Gedebage Main Market Bandung - Kamil, Indriyati; Rosimah, Siti; Rohmana, Rohmana; Maya Sari, Nur Zeina (LP2M INSURI Ponorogo, 2024)
Coconut waste, a largely untapped resource, holds immense potential for efficient utilization. However, this commodity's current production has yet to generate significant added value as coconuts are primarily used for coconut oil, and the fiber is often discarded as waste. This service research identifies challenges and communication barriers in using coconut dregs at the Gedebage Main Market, Bandung City. By employing the Community Research (CBR) service method through Forum Group Discussions (FGD), we aim to collaborate with the community to explore various approaches to the issues they face. Data was collected through a qualitative approach, including in-depth interviews, field observations, and literature studies. The service research findings reveal several challenges in utilizing coconut waste, such as infrastructure problems, licensing constraints, and the need for better-trained human resources. Meanwhile, communication obstacles faced include technical obstacles, namely the lack of accompanying staff or communicators who carry out outreach and provide information on the potential use of coconut dregs to the community. Technological obstacles include the unavailability of the required modern coconut waste processing machines. Institutional obstacles include unclear roles and responsibilities of the parties involved and the need for coordination between stakeholders in utilizing coconut waste. Your active participation and support are crucial in overcoming these obstacles and realizing the full potential of coconut waste.